EFEKTIVITAS PUTUSAN BADAN PENYELESAIAN SENGKETA KONSUMEN BERSIFAT FINAL DAN MENGIKAT BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (STUDI PUTUSAN PENGADILAN NEGERI KARAWANG NOMOR 45/PDT.SUS-BPSK/2022/PN KWG) - Jayanto Jayanto; Jeane Neltje Saly (Jurnal Hukum Adigama, 2022)
BPSK is a body tasked with handling and resolving disputes between business actors and consumers. BPSK is a special institution established and regulated in the Consumer Protection Act. This special institution established by the government has the main task of handling consumer disputes and can issue final and binding decisions as stipulated in Article 54 paragraph (3) of Law Number 8 of 1999 concerning Consumer Protection. efforts to object to the District Court as stipulated in Article 56 paragraph (2) of the Consumer Protection Law. The main issue is: How effective is the final and binding decision of the consumer dispute settlement agency based on Law Number 8 of 1999 concerning Consumer Protection? The author examines this problem by using normative legal research methods and using a statutory approach. The purpose of writing this law is to determine the effectiveness of BPSK decisions which are final and binding in the dispute resolution process. Research data shows that the BPSK decision is final and binding in its application, not effective, because the UUPK opens up opportunities for further legal action in the form of objections to the District Court.